Development of 'NutriFit Teen' Mobile Application on Adolescent Knowledge of Chronic Energy Deficiency (CED) Risk - Septian Mugi Rahayu; Eva Priskila; Adisurya Saputra (Jurnal Keperawatan Profesional (KEPO), 2026)
Chronic Energy Deficiency (CED) in adolescent girls has long-term effects on growth, reproductive health, and future productivity. Low knowledge of CED among adolescents is one of the main causes of this condition. The use of digital technology, particularly mobile applications, offers great potential for effectively improving adolescent nutrition literacy. This study aimed to develop and evaluate the effectiveness of the educational application "NutriFit Teen" in increasing adolescents' knowledge about the risks of CED. The design used was a quasi-experiment with a pretest and posttest approach with a control group. A total of 40 female adolescents aged 15–18 years were divided into two groups: intervention (n=20) and control (n=20). The instrument used was a questionnaire on KEK knowledge that had been tested for validity and reliability. The application was developed participatively and contains interactive information and daily reminders. Data analysis was performed using the Wilcoxon test. The results showed a significant increase in knowledge scores in the intervention group after using the application (p-value < 0.001). This study concluded that the “NutriFit Teen” application is effective in increasing adolescents' knowledge about the risks of KEK.